Perbandingan Nilai Metabolik Pada Mr-Spectroscopy Dengan Dan Tanpa Media Kontras Di Rsup Persahabatan Jakarta Timur - Ici Zuhra Wulandari Sekedang; I Putu Eka Juliantara; I Bagus Gede Dharmawan (Jurnal Ventilator, 2023)
Comparison Of Metabolic Value On MR-Spectroscopy With and Without Contrast Media at Persahabatan Hospital, East Jakarta. Magnetic Resonance Spectroscopy is a non-invasive technique that can be used to measure the metabolism of several biochemical components in body tissue, especially the brain. Based on observations made by the author at Persahabatan Hospital, the spectroscopy technique used at Persahabatan Hospital is a multi-voxle technique, with sequences selction namely s2D_PRESS_144, where the spectroscopy images are taken after administering contrast and prevalence for tumor cases in the Radiology Installation at Persahabatan Hospital, with 5 data from the month May-August 2023. To determine the validity of this opinion, the authors performed pre and post- contrast MR-Spectroscopy on patients with contrast and compared the results with patients without contrast. In this study the author used a quantitative analysis type of research with an experimental approach aimed at whether the administration of contrast material affects the results of MR-Spectroscopy in patients with brain tumor cases. Where the research data comes from primary data in the Radiology installation at Persahabatan Hospital from May - August 2023 using 5 patient data. Results: Based on an observational study carried out on primary data from 5 patients, there were differences in metabolic values with and without contrast media in brain tumor cases. And MR-Spectroscopy examination without contrast is better to use than with contrast, although from the overall data it turns out there are some data that say post- contrast is higher.